The Influence of Price, Location, Service, and Product Quality on Customer Satisfaction - Rudy Antoni Salim; Yudi Prayoga; Muhammad Ali Al Ihsan (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The retail business is a business that has very tight competition, as evidenced by a large number of retail outlets in each region. Therefore, it is necessary to know the factors that can make a retail business win the competition. Based on a literature study conducted by researchers, customer satisfaction is the most important factor to win the competition and get loyal customers. This study aims to analyze the effect of price, location, service, and product quality on consumer satisfaction at the supermarket of Brastagi Rantauprapat. This study used a quantitative approach with a sample of 247 people from 646 visiting populations. Data collection techniques were carried out using questionnaires or primary data. Data analysis techniques using descriptive statistics and multiple linear regression analysis. The results of the F test calculation research show simultaneously that the variables price, location, service, and product quality have a positive and significant effect on consumer satisfaction Fcount 30,135 > Ftable 2.37 with a significant value of 0.000 <0.05. The result of the determination value obtained is an R-value of 0.577 equal to 57.7% which indicates that the relationship between the variables of price, location, service, and product quality with consumer satisfaction has a fairly close relationship. The magnitude of the coefficient of determination is 0.332 or equal to 33.2%. This value means that 33.2% confirms that consumer satisfaction can be explained through the variables of price, location, service, and product quality. The remaining 66.8% is outside of this research variable.